Beyond the desert sands [large type] - Peterson, Tracie (Peterson, Tracie. Love on the Santa Fe, 2022)
"After living an opulent life with her aunt, the last thing Isabella Garcia wants is to celebrate Christmas in a small mining town with her parents. But she's surprised to see how much the town--and an old rival--have changed and how fragile her father's health has become. Faced with many changes, can she sort through her future and decide who she wants to be?"--Publisher description.